2013
DOI: 10.1021/jp404149n
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Molecular Theory of Homogeneous Bubble Nucleation: I. Equilibrium Embryo Definition

Abstract: We propose an equilibrium embryo definition for homogeneous bubble nucleation within the pure component superheated Lennard-Jones liquid. The suggested embryo definition serves as an improvement to a previous (n,v) embryo model (Uline and Corti 2007). In that model, the constrained equilibrium between the bubble and the surrounding superheated liquid was maintained by placing n particles within a spherical volume v, without concern for the redundant counting of configurations and the relevance of the model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Previous studies have investigated the minimum work for a bubble formation with two variables, taking into account bubble compressibility [41][42][43][44][45][46]. Here we use the two variables r and P g .…”
Section: B Free Energy For Bubble Formation and The Poynting Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the minimum work for a bubble formation with two variables, taking into account bubble compressibility [41][42][43][44][45][46]. Here we use the two variables r and P g .…”
Section: B Free Energy For Bubble Formation and The Poynting Correctionmentioning
confidence: 99%
“…In bubble nucleation, additional detail in the treatment of the process is required, in comparison to droplet nucleation, because of the variable vapor pressure and density in bubbles as they grow [41][42][43][44][45][46]. The vapor pressure in bubbles varies as they grow and has a significant effect on their growth rates and on the pre-exponential factor in the CNT formula for the nucleation rate.…”
Section: Introductionmentioning
confidence: 99%
“…b) Authors to whom correspondence should be addressed. Electronic addresses: christoph.dellago@univie.ac.at and cvaleriani@quim.ucm.es super-heated fluid has been recently studied in simple liquids (Lennard-Jones) using either the volume of the largest bubble as a local order parameter [6][7][8] or the density as a global one. 9 In recent work, Meadley and Escobedo 10 demonstrated that when comparing the nucleation free energy barrier obtained with the volume of the largest bubble to the one computed using the global density, the largest bubble volume is a better reaction coordinate than the density; it correlates more strongly with committor probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The largest one of these volumes is the preliminary volume ξ which we use to track the progress of the nucleation process. Note that a number of suitable bubble detection procedures have been suggested in the literature [28][29][30][31], which can all be used to obtain the preliminary volume ξ of the largest bubble in the system. In the second step, we calibrate the bubble volume v such that it corresponds to the average change in system volume due to the presence of such a bubble:…”
Section: A Simulation Detailsmentioning
confidence: 99%